2020
DOI: 10.3389/fphar.2020.01082
|View full text |Cite
|
Sign up to set email alerts
|

Shugan Decoction Alleviates Colonic Dysmotility in Female SERT-Knockout Rats by Decreasing M3 Receptor Expression

Abstract: Background: Irritable bowel syndrome (IBS) is a functional gut disease characterized by visceral hypersensitivity and gut motor dysfunction. Serotonin (5-hydroxytryptamine, 5-HT) is an important enteric neurotransmitter. High levels of 5-HT aggravate IBS symptoms. The serotonin reuptake transporter (SERT) is a membrane-embedded transporter involved in IBS pathogenesis that plays an important role in regulating 5-HT signaling. Aim: We investigated whether gut motor function was altered in SERT-knockout (SERT-KO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 28 publications
(29 reference statements)
2
7
0
Order By: Relevance
“…e present study showed that 5-HT induced colonic contractility was increased in the IBS group. e data was consistent with one recent study; the tension due to the ACh-induced colonic smooth muscle contractility was greater in serotonin reuptake transporter-knocked out rats than in wild-type rats [48]. Pretreatment with HJE and PEP inhibited the 5-HTinduced hypercontractility of the colon in the IBS rats.…”
Section: Discussionsupporting
confidence: 92%
“…e present study showed that 5-HT induced colonic contractility was increased in the IBS group. e data was consistent with one recent study; the tension due to the ACh-induced colonic smooth muscle contractility was greater in serotonin reuptake transporter-knocked out rats than in wild-type rats [48]. Pretreatment with HJE and PEP inhibited the 5-HTinduced hypercontractility of the colon in the IBS rats.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, we confirmed the VH and found dysmotility in female slc6a4 −/− rats. Moreover, we have reported the increased sensibility of colonic muscle strips to acetylcholine (ACh) isolated from female SERT KO rats, which may be related to the increased expression of muscarinic receptor 3 (M3 receptor) 41 . We can therefore utilize female slc6a4 −/− rats as a reliable IBS animal model.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we have reported the increased sensibility of colonic muscle strips to acetylcholine (ACh) isolated from female SERT KO rats, which may be related to the increased expression of muscarinic receptor 3 (M3 receptor). 41 We can therefore utilize female slc6a4 −/− rats as a reliable IBS animal model. Recent studies have reported that the serotonin system is involved in VH and gastrointestinal dysmotility.…”
Section: Discussionmentioning
confidence: 99%
“…The ingredients of SGD were analyzed by HPLC as reported in our previous study (Wang et al, 2020 ). Briefly, Saikosaponin A, paeoniflorin, 5-O-methylvisammioside, hesperidin, or cimicifugoside was dissolved in methanol and obtained 1 mg/mL of standard solution separately.…”
Section: Methodsmentioning
confidence: 99%